Architecture tradeoffs of integrating a mesh generator to partition of unity enriched object-oriented finite element software - Dunant, Cyrille; Vinh, Phu Nguyen; Belgasmia, Mourad; Bordas, Stéphane; Guidoum, Amor (European Journal of Computational Mechanics, 2007)
We explore the tradeoffs of using an internal mesher in a XFEM code. We show that it allows an efficient enrichement detection scheme, while retaining the ability to have welladapted meshes. We provide benchmarks highlighting the considerable gains which can be expected from a well designed architecture. The efficiency of the proposed algorithm is shown by solving fracture mechanics problems of densely micro-cracked bodies including adaptive mesh refinement.